2012
DOI: 10.1089/vbz.2011.0779
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Peptide-Based ELISA for Serological Diagnostics: A Retrospective Study of Human Monkeypox Infection

Abstract: Although smallpox has been eradicated, other diseases caused by virulent orthopoxviruses such as monkeypox virus (MPV) remain endemic in remote areas of western and central sub-Saharan Africa, and represent a potential biothreat due to international travel and/or inadvertent exposure. Unfortunately, extensive antigenic cross-reactivity among orthopoxviruses presents a challenge to serological diagnosis. We previously reported a 20mer peptide-based ELISA that identified recent MPV infection with > 90% sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…1 , when we truncated the 3p-2 peptide to 83 WDPQELDILGSQ 94 and 75 QALNTTLPWDPQEL 88 which contain the minimal conserved epitope, the reactivity of the polypeptide decreased significantly although the OD 450 value was still positive. The similar results have been reported in previous study, which described that peptide length alters diagnostic sensitivity and specificity [ 15 ]. In the same report, the authors suggested that conjugation of peptides to BSA could improve assay sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…1 , when we truncated the 3p-2 peptide to 83 WDPQELDILGSQ 94 and 75 QALNTTLPWDPQEL 88 which contain the minimal conserved epitope, the reactivity of the polypeptide decreased significantly although the OD 450 value was still positive. The similar results have been reported in previous study, which described that peptide length alters diagnostic sensitivity and specificity [ 15 ]. In the same report, the authors suggested that conjugation of peptides to BSA could improve assay sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…Immunodiagnostic tests based on peptide serology offer several advantages over others that rely on more complex biological materials. The fact that synthetic peptides are not derived from biological material but are in fact chemically defined antigens greatly simplifies assay standardization and validation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, MPXV may also cause subclinical infections which might account for seroconversion in some people [ 42 ]. Promising MPXV-specific peptide-based ELISAs might be useful in differentiating between MPXV-specific antibodies and anti-OPV antibodies in the future [ 43 ].…”
Section: Discussionmentioning
confidence: 99%